An age of infidels the politics of religious controversy in the early United States - Schlereth, Eric R. (Philadelphia University of Pennsylvania Press, 2013)
Eric R. Schlereth places religious conflicts between deists and their opponents at the center of early American public life. This history recasts the origins of cultural politics in the United States by exploring how everyday Americans navigated questions of religious truth and difference in an age of emerging religious liberty.
Cover -- Title -- Copyright -- Contents -- Introduction. Remaking Religion -- Chapter 1. Boundaries -- Chapter 2. America's Deist Future -- Chapter 3. Citizen Deists -- Chapter 4. Partisan Religious Truths -- Chapter 5. America's Deist Past -- Chapter 6. Free Enquiry -- Chapter 7. Political Religion, Political Irreligion -- Epilogue. The Origins of American Cultural Politics -- Notes -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Acknowledgments.
""Acknowledgments""
Based on the author's thesis from Brandeis Univ., 2008
Includes bibliographical references and index
Electronic reproduction; Available via World Wide Web
Online-Ausg.
Keywords: Church and state -- United States -- History; Deism -- United States -- History; Christianity and politics -- United States -- History; Christianity and culture -- United States -- History; Christianity and other religions -- United States; Christianity and politics -- United States -- History; Christianity and culture -- United States -- History; Christianity and other religions -- United States; Church and state -- United States -- History; Deism -- United States -- History; United States -- Politics and government -- 1783-1865; Christianity and culture ; United States ; History; Christianity and other religions ; United States; Christianity and politics ; United States ; History; Church and state ; United States ; History; Deism ; United States ; History; United States ; Politics and government ; 1783-1865; Electronic books; United States -- Politics and government -- 1783-1865